Maximum mouth opening of ethnic Chinese in Taiwan - Kuang-Ta Yao; Chia-Cheng Lin; Chao-Ho Hung (Elsevier, 2009)
Maximum mouth opening (MMO) is a significant diagnostic reference for many clinical conditions. However, the number of relevant studies is limited, and the relationship between age and MMO has not yet been established. The purpose of this study was to measure and analyze the MMO of ethnic Chinese adults in Taiwan and to examine the possible relationship between age and MMO. Materials and methods: A total of 1442 adult ethnic Chinese (Taiwanese) subjects aged 20-80 years (705 males, 737 females) were randomly selected. Subjects were divided into three age groups: 20-39 years (young), 40-59 years (middle), and ≥ 60 years (senior), and their maximum voluntary mouth opening was measured. Independent sample t test and one-way ANOVA followed by the post hoc Scheffé test were used to examine differences in MMO relative to sex and age groups. A simple linear regression model was used to estimate the relationship between MMO and age. Results: The average MMO for sample subjects was 49.10 ± 6.30 mm, and the MMO of males (49.92 ± 6.55 mm) was significantly larger than that of females (48.32 ± 5.95 mm; P < 0.001). MMO significantly decreased with increasing age, regardless of sex. The average MMO values were 51.11 ± 6.47 mm, 48.45 ± 5.76 mm, and 46.62 ± 5.71 mm for the young, middle and senior age groups, respectively (P < 0.001). In the regression model, it was estimated that for every 10 years, MMO decreased by about 1.4 mm in males and 0.9 mm in females. For the age range of 20-80 years, the regression equation is: MMO (mm) = 56.60−0.14×age, for males; and MMO (mm) = 52.33−0.09×age, for females. Conclusion: Within the limits of this study, we concluded that both sex and age have significant influences on the MMO value of ethnic Chinese in Taiwan, and age is a significant predictor of MMO measurements.